Phase transitions and interface phenomena in the cryogenic temperature domain of a niobate nanostructured ceramic - Lanfredi, S. [UNESP]; Darie, C.; Bellucci, F. S.; Colin, C. V.; Nobre, Marcos Augusto Lima [UNESP] (Royal Soc Chemistry, 2014)
Powder neutron diffraction and dielectric spectroscopy were used to investigate both crystallographic and dielectric permittivity properties of a Sr2KNb5O15 single phase ferroelectric oxide with nanosized grains ranging from 35 nm to 90 nm. Measurements were carried out in the temperature range from 10 K (cryogenic) to 550 K. All neutron diffraction data were indexed on the basis of a tetragonal double unit cell. From 10 K to room temperature the space group of the Sr2KNb5O15 ferroelectric phase was considered to be P4bm. The refinement of the paraelectric phase (at 550 K) was determined in the centrosymmetric space group P4/mbm. Dielectric spectroscopy measurements were performed in a thermal cycle. A set of four phase transitions non-related to symmetry changing was detected from Rietveld analysis of neutron powder diffraction data. During a thermal cycle, in the cryogenic temperature domain, strong thermal hysteresis is developed. Both phase transition and thermal hysteresis were correlated. These phenomena are associated with Nb-cation atomic displacements in the NbO6 octahedra along the c-axis direction and of the domain with different frequencies involving grains as well as an excess of interfaces ascribed to the grain boundary. The bulk/grain boundary interfaces in nanostructured ceramics are correlated with the thermal stability phenomenon.